A study to assess the knowledge, attitude and practice of mothers related to poisoning among under five children in selected hospital, Chennai - Ariya S Kurup; Dr. Sathiyalatha Sarathi; Dr. V. Hemavathy (The Bioscan, 2025)
Introduction: Mothers' knowledge about poisoning is significantly influenced by their educational background, socio-economic status, and the age of their children. Aim of the study: The study aimed to assess the knowledge, attitude and practice of mothers related to poisoning among under five children in selected hospital, Chennai. Methodology: This study employed a descriptive design. The study was conducted at a selected hospital in Chennai, with a total of 120 mothers of children aged below five years participating in the study. A convenient sampling technique was used to select participants who met the inclusion criteria, which included mothers of children aged below five years who were willing to participate in the study. Mothers of children older than five years or those unwilling to participate were excluded from the study. Results: The study assessed mothers' knowledge, attitude, and practices (KAP) regarding poisoning in children under five years. The results revealed that 66.67% of mothers demonstrated good knowledge, 75% had a positive attitude, and 70.83% followed good safety practices. However, 25% of mothers exhibited average levels in all three areas, and 8.33% displayed poor knowledge, negative attitudes, and inadequate practices. The correlation analysis showed positive relationships between knowledge and attitude, and between attitude and practice, indicating that better knowledge leads to more positive attitudes and safer practices. Conclusion: The study concluded that majority of mothers have good knowledge, positive attitudes, and follow appropriate safety practices regarding poisoning prevention in young children, there is still room for improvement.